DEVELOPING INTEGRATED-ACOUSTIC LEARNING MODEL BASED ON BANYUWANGI LOCAL CULTURE FOR CHARACTER GROWTH OF FIRST CLASS STUDENTS PRIMARY SCHOOL - Martadi Martadi; Diana Nomida Musnir; Yufiarti Yufiarti (Universitas Sebelas Maret, 2019)
This research aims to develop an integrated thematic learning model based on Banyuwangi local culture for the development of elementary school students' character. A developmental research by using the Analysis, Design, Development, Implementation and Evaluation model is undertaken. The results of this research show that from the aspect of material feasibility, the result of 87% gives value 4 (Very Good) and 13% gives value 3 (Good). In terms of graphing eligibility, 89% of respondents rated 4 and 11% to give value 3. In terms of legibility verification, members rated 90% of the value 4 and 10% gave the value 3. In terms of media qualifications of 99% possible media according to the efficiency to be achieved. The results of the limited trial in elementary school, the feasibility of the teacher's faculty aspect assessed as much as 49% of value 4 and 51% giving value 3. The feasibility of the graphing, known as 61% gives the value of 4 and as much as 39% gives the value 3. Aspect feasibility readiness, 90 % gives value 4 and 10% gives value 3. Media qualification, known as 100% states fit according to content, passion, suitability of children, and conformity to the cultural arts of Banyuwangi. As a conclusion, that transfering the cultural moral value towards the student-oriented learning center, has established active and fun learning to make the students more motivated.